Formal Education Of Administrative Officials In The Republic Of Croatiatopic Article - Romić, Danijela; Halak, Željka Vajda (European Scientific Journal, ESJ, 2016)
It is an indisputable fact that the administrative officials are a key factor for quality, efficient and good administration. Administrative officials are educated in-service also but in this paper we will focus on formal training programs for potential candidates for state and public administration. Binary system of higher education is established in accordance with the Bologna process. The professional study should, through their study programs, train students for specific skills and competences required in the labor market. The best ways to acquire certain skills are the practical work and learning. For the purpose of this paper the authors compare eight existing professional programs of administrative studies, in particular by analyzing the way of implementation and length of professional practice. Professional practice is one of the fundamental subjects where students are trained for specific tasks.